Professor Edward Drinker Cope’s Travels Through North Carolina, August–December 1869: Insights from the Transcriptions and Annotations of Letters to His Father and His Contributions to North Carolina Ichthyology - Bryn H. Tracy; Robert E. Jenkins (Southeastern Fishes Council Proceedings, 2021)
Since 1870, ichthyologists have pondered Edward Drinker Cope’s two publications: “On some Etheostomine Perch from Tennessee and North Carolina” and “A Partial Synopsis of the Fishes of the Fresh Waters of North Carolina”, along with correspondences to his father while traveling in North Carolina. We transcribed and annotated four of his letters searching for further knowledge regarding his field notebook(s) and original data (meristics, morphometrics, life coloration, etc.) from his travels across NC during Summer and Fall of 1869. However, unresolved questions remained - many related to unaccounted for periods of time. We did not achieve insights into who helped him with his collections. The loss of some of his larger specimens or their unavailability to be re-examined by Cope at a later date, lead us to question if Cope hastily wrote some of the descriptions in the field, or wrote them from memory afterwards in his lodging, or did he write them in a field notebook? We did not discover the existence or whereabouts of field notes or field book. We surmised he did record field notes and original data, because he could not have remembered meristic counts and which data went with which species after encountering a myriad of specimens in the field. We marveled how Cope was able to successfully achieve the rapidity in naming, writing, and publishing shortly after his trip. We concluded Cope must have been extremely impatient and perhaps consumed by his more important paleontological interests when writing two fish manuscripts in a short period of time. Cope’s two publications resulting from this trip laid a foundation for all ensuing studies of NC’s freshwater fish fauna the past 151 years. Of the 242 described species of freshwater fish in NC 45 were described by him between 1865-1871. He described 25 species from his NC trip of which 15 species are presently considered valid; the other species having since been synonymized. Cope recounted collecting 91 described and undescribed species from NC during his trip, excluding four genera, Acipenser, Carpiodes, Ictiobus, and Sander (Stizostedion), whose specimens were lost, unavailable, or unseen. We accounted for all of the species and specimens he had collected during this trip. Lots, totaling 138, representing 63 species and 943 specimens were subsequently curated at Academy of Natural Sciences of Drexel University, the National Museum of Natural History, and the University of Michigan Museum of Zoology. No additional lots were found at other museums. Various type specimens are represented in 49 lots, with the remaining 89 lots representing non-type specimens.
Keywords: Edward Drinker Cope; North Carolina; Historical Ichthyology